A Discourse Analysis of Grammatical Cohesion in News Item Text of "Symphony 3" XII Grade English Textbook - Nurwahidah Nurwahidah; Didin Nuruddin Hidayat; Nida Husna; Alek Alek (Journal of English Language Teaching and Linguistics, 2022)
This study aims to (1) determine the kind of grammatical cohesion devices that were used in a news item text of a textbook (2) to examine how reference, substitution, ellipses, and conjunction were used to describe the Cohesion that was used in the news item text of an English textbook for senior high school students in the 12th grade "Symphony 3". This study is qualitative descriptive research. The analysis of data found that the grammatical cohesion devices in the news item text of the textbook are reference, conjunction, and ellipsis. References become the most common devices, followed by conjunction and ellipsis. Surprisingly, there is no substitution found in this text. Hence, substitution and ellipsis are the two most minor common forms of cohesive devices. It demonstrates that the two types of coherent devices have no use in written discourse. The news item text of the textbook is written cohesively "good" as the percentage is 61 % for the reference. In comparison, 38% for the conjunction is categorized as "fair." This textbook is considered an objective criterion of cohesiveness. It may be fascinating to analyze these in separate studies in spoken discourse, particularly spontaneous speech.